Operating Field Optimization of Giant Magneto Impedance (GMI) Devices in Micro Scale for Magnetic Bead Detection - Kim, Dohun; Kim, Hyungkyung; Park, Sunhee; Lee, Wooyoung; Jeung, Won Young (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
Giant magneto impedance (GMI effect devices for magnetic bead detections were examined. Since commercialized magnetic beads in biological applications are superparamagnetic in nature, not only for improvement of maximum sensitivity but also precise optimizations of operating fields are crucial for sensor applications. We have found that operating fields and maximum sensitivity can be enhanced by the tailoring aspect ratio in microscopic GMI sensors. With an aspect ratio of 3.3-3.8, the GMI sensors were found to exhibit an overall GMI ratio of more than 110% and a maximum sensitivity of 1.61 mV/Oe (15.4%/Oe) at the operating field of 43.1 Oe. Our results demonstrate that microscopic GMI sensors are highly sensitive to magnetic bead detections.
Keywords: SENSORS